Outdoor Air Pollution and Brain Structure and Function From Across Childhood to Young Adulthood: A Methodological Review of Brain MRI Studies - Herting, Megan M.; Younan, Diana; Campbell, Claire E.; Chen, Jiu-Chiuan (Frontiers in Public Health, 2019)
Outdoor air pollution has been recognized as a novel environmental neurotoxin. Studies have begun to use brain Magnetic Resonance Imaging (MRI) to investigate how air pollution may adversely impact developing brains. A systematic review was conducted to evaluate and synthesize the reported evidence from MRI studies on how early-life exposure to outdoor air pollution affects neurodevelopment. Using PubMed and Web of Knowledge, we conducted a systematic search, followed by structural review of original articles with individual-level exposure data and that met other inclusion criteria. Six studies were identified, each sampled from 3 cohorts of children in Spain, The Netherlands, and the United States. All studies included a one-time assessment of brain MRI when children were 6-12 years old. Air pollutants from traffic and/or regional sources, including polycyclic aromatic hydrocarbons, nitrogen dioxide, elemental carbon, particulate matter (<2.5 or <10 µm), and copper, were estimated prenatally (n=1), during childhood (n=3), or both (n=2), using personal monitoring and urinary biomarkers (n=1), air sampling at schools (n=4), or a land-use regression modeling based on residences (n=2). Associations between exposure and brain were noted, including: smaller white matter surface area (n=1) and microstructure (n=1); region-specific patterns of cortical thinness (n=1) and smaller volumes and/or less density within the caudate (n=3); altered resting-state functional connectivity (n=2) and brain activity to sensory stimuli (n=1). Preliminary findings suggest that outdoor air pollutants may impact MRI brain structure and function, but limitations highlight future studies are necessary that include adolescents and young adults, as well as longitudinal multi-modal MRI outcomes.